Integrating lineament density in the DRASTIC model for better groundwater assessment - Nursabrina Syahirah Hairudin,; Norhayati Mat Rawi,; Norsyafina Roslan,; Norbert Simon, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Forecast of groundwater potential zones is essential, especially in areas where surface water is not sufficient during the dry season, such as the Tampin District, Negeri Sembilan, Malaysia. In the literature, the lineament parameter is often combined with a groundwater assessment model such as the DRASTIC model. However, most of these practices do not follow the procedure of assigning weight to the parameter as used in the model, so many researchers assign different ranges of weights to the lineament parameter. Therefore, this study focuses on how to systematically incorporate a lineament density map into the existing DRASTIC model based on the specific range of weight specified by the model; thus, the inclusion of more geological input will improve the model performance. DRASTIC is an abbreviation for the parameters used in the model: Depth to water; Recharge; Aquifer media; Soil media; Topography; Impact to vadose zone; and Conductivity (hydraulic). The addition of the lineament density map has successfully improved the performance of the DRASTIC model from 50 to 80% based on the distribution of 30 producing wells in the Tampin District, where the geology and lineament density play major roles in determining the potential groundwater area.